Exploring students’ English language use in multimodal computer-mediated communication tasks: A case study of a university in Indonesia - AbdulQodir, Muntaha (Curtin University, 2024)
This research investigated the experiences of Indonesia university students while completing multimodal CMC tasks via Instagram based on sociocognitive approach. Findings indicated that using Instagram’s text, audio and video chat features enhanced students’ motivation and engagement, confidence, willingness to communicate and digital literacy. The use of nonverbal cues during these tasks facilitated their expression of emotions, humour and appreciation. Nonverbal cues (e.g., emojis and gestures) contributed to building multimodal interactive alignment which fostered language learning and use.